2023
DOI: 10.46827/ejefr.v7i1.1431
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Factors Influencing Purchasing Behaviour of Online Consumers in Klang Valley, Malaysia

Abstract: <p>This study aims to analyse and discuss the factors influencing purchasing behaviours of online consumers in Klang Valley, Malaysia. In the past few years, the world has been evolving at light speed, and consumers must keep up with this fast-paced development. The technological era has changed purchasing habits so much that consumers have turned to online shopping, and vendors have explored the digitalization of product search and sales. With the impact of the pandemic, the digital age has taken over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Additionally, research has highlighted the importance of perceived risk as a factor in online shopping behavior, with psychological risks leading to difficulties, loss of trust, and negative psychological effects on consumers [24]. In the context of Malaysia, a study found that consumers' perceived risks of online shopping directly influence their attitude towards online shopping behavior [6], [11], [25], [26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, research has highlighted the importance of perceived risk as a factor in online shopping behavior, with psychological risks leading to difficulties, loss of trust, and negative psychological effects on consumers [24]. In the context of Malaysia, a study found that consumers' perceived risks of online shopping directly influence their attitude towards online shopping behavior [6], [11], [25], [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The popularity of e-commerce is growing due to the convenient, affordable, and accessible shopping experience. Consumers today are too busy to visit physical stores, and online shopping allows them to shop from the comfort of their own homes [4]- [6]. Additionally, online shopping often provides lower prices compared to traditional brick-and-mortar stores, which is another factor that attracts consumers to online shopping [2], [4], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations